Customer Loyalty Model of Adhesive Tape Business in Thailand - Neewong, sangduan; Kortana, Tanapol (Modern Management Frontier Journal, 2024)
This research aims to investigate the customer loyalty model of Adhesive Tape Business in Thailand. This research was mixed methods approach: qualitative and quantitative research design using convergent parallel design. The online questionnaire used as an instrument for collecting data from 340 customers of Adhesive Tape Business in Thailand and used interview questionnaire as an instrument for collecting data by in-depth Interview from 20 executive and experts in product management of Adhesive Tape Business in Thailand. The variables consisted of two endogenous latent variable:customer satisfaction and customer loyalty; and three exogenous latent variable: service quality, service innovation, and brand image.These latent variables were measured by 17 observed variables. All the composite reliability values ranged from 0.741 to 0.769. Data was analyzed by SEM. The results show that quantitative research and qualitative research are consistent. In addition, the results indicate that the highest level factor influencing the customer satisfaction directly influenced customer loyalty.Moreover, subordinate highest level factor influencing the service quality directly influenced customer loyalty. Additionally, the results of this study indicate that customer loyalty model of Adhesive Tape Business in Thailand was in congruence with the empirical data.This model exhibits goodness of fit.